Treatment of post-transplantation lymphoproliferative disorders after kidney transplant with rituximab and conversion to m-TOR inhibitor. (Colombia Medica, 2016)
Background:Post-transplantation lymphoproliferative disorders are serious complications of organ transplantation which treatment is not yet standardized.Objective:To describe the clinical response, overall and graft survival of patients in our center with this complication after kidney transplantation, which received rituximab as part of their treatment as well as conversion to m-TOR.Methods:Retrospective study, which included patients, diagnosed with post-transplant lymphoproliferative disorders after kidney transplantation from January 2011 to July 2014.Results:Eight cases were found with a wide spectrum of clinical presentations. Most had monomorphic histology, 85% were associated with Epstein-Barr virus, 25% of patients had tumor involvement of the renal graft, and 12.5% ​​had primary central nervous system lymphoma. All patients were managed with reduction of immunosuppression, conversion to m-TOR (except one who lost the graft at diagnosis) and rituximab-based therapy. The overall response rate was 87.5% (62.5% complete response, 25% partial response). Survival was 87.5% with a median follow-up of 34 months. An additional patient lost the graft, with chronic nephropathy already known. All the remaining patients had stable renal function.Conclusions:There are no standardized treatment regimens for lymphoproliferative disorders after kidney transplantation, but these patients can be managed successfully with reduction of immunosuppression, conversion to m-TOR and rituximab-based schemes.